Intra- and Extraoral Signs of Probable Bruxism (Scoping Review) - Carolina Marpaung; Yoseph Kusnadi; Yenny Pragustine (Indonesian Dental Association, 2022)
Bruxism is a repetitive masticatory muscle activity that has received attention in dental literature for its association with dental restoration failures, orofacial pain, neurological disease, and obstructive sleep apnea. As a determining factor in the diagnosis, parameters regarding the type and classification of intraoral and extraoral signs of probable bruxism are needed. This study aimed to identify the intraoral and extraoral signs of bruxism in the literature. A literature search was performed in the National Library of Medicine (PubMed) to identify all the articles published assessing intra and extraoral signs of bruxism. The selected articles were then screened and structurally read by three persons and summarized in PICO tables. Out of 551 initially retrieved references, 39 articles met the inclusion criteria and were thus included in the scoping review. The studies were divided into six categories based on the type of oral signs: buccal mucosa ridge (n=4), masseter hypertrophy (n=3), tongue indentation (n=4), tooth fracture (n=5), torus mandibularis (n=3), and tooth wear (n=20). This study concluded that the available studies utilize various methods in subjective and clinical data collection. Buccal mucosa ridge, tongue indentation, and torus mandibularis were common in subjects with bruxism. The association of masseter hypertrophy and tooth fracture with bruxism is not conclusive. Although studies on tooth wear in bruxism subjects are the most prevalent among other oral signs, no study has been able to establish a direct link between bruxism and tooth wear.